Uniform Dispersion of Multiwalled Carbon Nanotubes in Copper Matrix Nanocomposites Using Metal Injection Molding Technique. (2nd October 2013) - Muhsan, Ali Samer; Ahmad, Faiz; Mohamed, Norani M.; Megat Yusoff, Puteri Sri Melor; Rafi Raza, Muhammad
Abstract : This work presents a novel fabrication approach of multiwalled carbon nanotubes (MWNTs) reinforced copper (Cu) matrix nanocomposites. A combination of nanoscale dispersion of functionalized MWNTs in low viscose media of dissolved paraffin wax under sonication treatment followed by metal injection molding (MIM) technique was adopted. MWNTs contents were varied from 0 to 10 vol.%. Information about the degree of purification and functionalization processes, evidences on the existence of the functional groups, effect of sonication time on the treated MWNTs, and microstructural analysis of the fabricated Cu/MWNTs nanocomposites were determined using TEM, EDX, FESEM, and Raman spectroscopy analysis. The results showed that the impurities of the pristine MWNTs such as Fe, Ni catalyst, and the amorphous carbon have been significantly removed after purification process. Meanwhile, FESEM and TEM observations showed high stability of MWNTs at elevated temperatures and uniform dispersion of MWNTs in Cu matrix at different volume fractions and sintering temperatures (950, 1000 & 1050°C). The experimentally measured thermal conductivities of Cu/MWNTs nanocomposites showed remarkable increase (11.25% higher than sintered pure Cu) with addition of 1 vol.% MWNTs, and slight decrease below the value of sintered Cu at 5 and 10 vol.% MWNTs.